Feeding Behavior and Adaptation to Culture Conditions in Black Sea Flounder (Platichthys flesus luscus) - Birol Baki; Hakan Baki (Turkish Journal of Agriculture: Food Science and Technology, 2016)
The aim of this study was to determine the growth parameters of European Flounder fry (Platichthys flesus luscus L. 1758) caught from the nature in different feeding methods in aquaculture conditions. The study was conducted between April and July 2011, and the fish were collected at the connection point of Sarıkum Lagoon with the Black Sea in Sinop Province using seines and large scoops. A total of 750 European Flounder with the average weight of 0.93±0.01 (0.71-1.21) g were stocked in 5 groups with 3 repetitions. The groups were organized according to the feeding protocols [G1:90 days Chironomid larvae (CL), G2:60 days CL+30 days CL+ granular feed (GY), G3:30 days CL+60 days CL+ GY, G4:90 days CL+GY, G5:90 days GY]. At the end of the study, the weights of the fish were determined as 10.83±0.51, 9.89±0.22, 6.33±0.21, 5.13±0.11, 3.81±0.09, respectively. It was found that feeding preferences of the fish had significant effects on weight gain, specific growth rate, feed conversion ratio and survival rate. European Flounder fry, as in their natural habitat, mostly preferred natural feed moving in the deep in the production site. It was determined that using live feed as the starter feed for the adaptation of European Flounder fry had a significant effect on growth parameters and survival rates.